Evaluating the athletics Athletes' Physical Fitness for PON XXI/2024 Qualification - Tahapary, Johni M.; Matitaputty, Johanna; Rumawatine, Ztella (KnE Social Sciences, 2024)
Maluku's achievements can grow when the human resources of the coaches are enhanced to promote professionalism in the development of the science and technology of sports. Thus, the training process is not solely based on experience but on the science of training, which is studied in depth to support the better development of training athletes in the future. This study aims to determine how well Maluku athletic athletes' physical fitness is prepared for the PON XXI/2024 qualification round held in Solo, Central Java. This study used saturation sampling to study all the population samples. The instruments utilized in this study are the VO2 Max test, local muscle endurance test, biomotor ability test, speed and power tests, and local muscular stamina tests. The results revealed that the athletes' physical fitness to face a national event, in this case, the PON XXI/2024 qualification, is still considered medium, and the physiological condition belongs to the category of good based on the running time achievement that is close to the time achieved on the PON XXI qualification. The results of the study indicate that Maluku's athletic athletes have improved. However, the improvement has not surpassed the PB PASI time record. Despite the improvement in performance during training, the athletes had not reached the target to pass into the PON XXI Qualification. Keywords: evaluation, physical fitness, athletes’ achievement.